The Russian Federation in Transition : External Developments - Christensen, Benedicte (Occasional Papers; Occasional Paper ;, 1994)
This paper examines the effects of three "shocks" - the disintegration of the U.S.S.R., domestic economic reform, and changing relations with other countries- on Russia's balance of payments position. The importance of consistent economic reform and a liberal trade regime is stressed, together with the role of financial assistance.